2008
DOI: 10.1186/1471-2474-9-28
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of osteoporosis risk factors in Iranian women compared with Indian women

Abstract: Background: Osteoporosis is an important public health problem in older adults. It is more common in postmenopausal women and not only gives rise to morbidity but also markedly diminishes the quality of life in this population. There is lack of information about the risk factor of osteoporosis in developing countries. In this study we aimed to assess the risk factors for osteoporosis in postmenopausal women from selected BMD centers of two developing Asian countries (Iran and India).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 33 publications
6
77
2
5
Order By: Relevance
“…Smoking was not shown to be associated significantly with osteoporosis in our study; this is contrary to the findings of some other studies in which smoking was considered a significant factor [17][18][19]. We think that the reason may be under-reporting of smoking among our participants because all of them were females living in a conservative community.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Smoking was not shown to be associated significantly with osteoporosis in our study; this is contrary to the findings of some other studies in which smoking was considered a significant factor [17][18][19]. We think that the reason may be under-reporting of smoking among our participants because all of them were females living in a conservative community.…”
Section: Discussioncontrasting
confidence: 56%
“…Menarche after age 14 years is associated with increased incidence of osteoporosis. This risk factor is most likely associated with estrogen deprivation [19].…”
Section: Introductionmentioning
confidence: 99%
“…This disease causes increase of health care expenses, physical and psychological complications and decreased quality of life that all have negative effects on the affected individual, his/her family and the society. For this, it has been known as a major general health problem [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The level of bone mineral density between the groups was statistically significant (p<0.001). In this regards Keramat et al, 24 reported that the prevalence of lumber spine osteoporosis and osteopenia in the postmenopausal women was 26.5% and 50% respectively.…”
Section: Discussionmentioning
confidence: 95%